Follicular development in a 7-day versus 4-day hormone-free interval with an oral contraceptive containing 20 mcg ethinyl estradiol and 1 mg norethindrone acetate - Rible, Radhika D.; Taylor, DeShawn; Wilson, Melissa L.; Stanczyk, Frank Z.; Mishell, Daniel R. (Contraception (Stoneham), 2009)
Combined oral contraceptive (COC) formulations with 20 mcg ethinyl estradiol (EE) have a greater incidence of ovarian hormone production and follicular development, which can be managed by shortening the number of hormone-free days per COC cycle. This study evaluates differences in follicular development during a 7-day versus 4-day hormone-free interval in a COC regimen with 20 mcg EE and 1 mg norethindrone acetate. Forty-one healthy women were randomized in an open-label fashion to this formulation in either a 24/4 or a 21/7 day regimen for three cycles. Estradiol, progesterone, follicle-stimulating hormone, luteinizing hormone and inhibin B were measured daily from Cycle 2, Day 21 to Cycle 3, Day 3 and on Day 7 of Cycle 3. Follicular diameter and Hoogland score were calculated on Cycle 2, Days 21, 24 and 28 and Cycle 3, Days 3 and 7. Sixty-six percent of subjects in the 21/7 group and 70% of the subjects in the 24/4 group developed a follicle greater than 10 mm diameter. Ovarian steroid hormone levels, Hoogland scores and bleeding patterns were not statistically significant between the groups. In contrast to prior studies, this analysis suggests no difference in follicle development or bleeding patterns among women receiving a 21/7 or 24/4 regimen of a 20-mcg EE/1-mg norethindrone acetate COC.